(untitled) (Faridpur Medical College Journal, 2013)
Unmet need for family planning is the key indicator to achieve Millennium Development Goal by the year 2015. Bangladesh Government has a great success in family planning sector but population has almost doubled in recent years. This study was carried out among married women to compare the determinants of unmet need for family planning among rural and urban communities during the period from July 2010 to June 2011. Unmet need for family planning in rural community was found 18(12%) and in urban community it was 38(25.3%). Among rural women unmet need for limiter was 13(8.6%) and spacer was 5(3.4%) while limiter 29(19.4%) and spacer 9(5.9%) found among urban women. Mean age at marriage was found 17.97(SD±2.66) years and mean age at first child birth was 19.91(SD±2.71) years among rural women. Among urban women mean age at marriage was found 20.43(SD±4.08) years and mean age at first child birth was 22.55 (SD±4.3) years. Current contraceptive users among rural women was 7 9(52.7%) while it was 61(40.7%) among urban women. In this study, association between unmet need for family planning and freedom of choice of contraceptives was highly significant (p=0.001). To increase contraceptive prevalence rate and reduction of unplanned pregnancy, more emphasis should be given on unmet need for family planning. DOI: http://dx.doi.org/10.3329/fmcj.v8i1.16894 Faridpur Med. Coll. J. 2013;8(1): 26-30